2013
DOI: 10.1088/1367-2630/15/3/035002
|View full text |Cite
|
Sign up to set email alerts
|

Micro-rheological behaviour and nonlinear rheology of networks assembled from polysaccharides from the plant cell wall

Abstract: The same fundamental questions that have driven enquiry into cytoskeletal mechanics can be asked of the considerably less-studied, yet arguably just as important, biopolymer matrix in the plant cell wall. In this case, it is well-known that polysaccharides, rather than filamentous and tubular protein assemblies, play a major role in satisfying the mechanical requirements of a successful cell wall, but developing a clear structure-function understanding has been exacerbated by the familiar issue of biological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…This behaviour has indeed been reported previously in these acidinduced pectin gels where the data were shown to be consistent with the Glassy Wormlike Chain model, 28 which also captured the reported microrheology of the system. 13 In general stress-stiffening of networks has been shown to be a generic feature of systems in which the fundamental connecting elements deform according to a worm-like chain Hamiltonian. 29 It is worthwhile noting that at least in the accessible pre-stress region that the increase of the differential shear modulus with pre-stress appears to increase linearly rather than with a power of 3/2 as predicted by the simple model.…”
Section: Rheology and Tem Of A Pre-formed Acid-induced Gelmentioning
confidence: 99%
“…This behaviour has indeed been reported previously in these acidinduced pectin gels where the data were shown to be consistent with the Glassy Wormlike Chain model, 28 which also captured the reported microrheology of the system. 13 In general stress-stiffening of networks has been shown to be a generic feature of systems in which the fundamental connecting elements deform according to a worm-like chain Hamiltonian. 29 It is worthwhile noting that at least in the accessible pre-stress region that the increase of the differential shear modulus with pre-stress appears to increase linearly rather than with a power of 3/2 as predicted by the simple model.…”
Section: Rheology and Tem Of A Pre-formed Acid-induced Gelmentioning
confidence: 99%
“…In the same way, time-dependent external or internal stresses may be incorporated into the model [42], e.g., to represent the activity of molecular motors or the stresses arising from the confinement and polymerization. The GWLC has quite successfully been employed to parameterize power-law rheology and strain stiffening in actin [90,67] and pectin [120] networks as well as in cells [41].…”
Section: Viscoelastic Models and The Gwlcmentioning
confidence: 99%
“…The structural features most often discussed in relation to its in vivo functionality are also those frequently listed as the basis for its technological and economical attributes, which focus on its ability to crosslink with divalent cations to alter the texture of foods and the rheology of water (Axelos, Lefebvre, Qiu, & Rao, 1991;Kim et al, 2013;Kim et al, 2014;Luzio & Cameron, 2007;Ngou emazong, Nkemamin, et al, 2012;Ross et al, 2011;Van Buggenhout, Sila, Duvetter, Van Loey, & Hendrickx, 2009;Van Buren, 1979;Vincent, Mansel, Kramer, Kroy, & Williams, 2013) and to stabilize acidified milk drinks (Jensen, Rolin, & Ipsen, 2010;Tromp, de Kruif, van Eijk, & Rolin, 2004). Pectin's functionality is mostly related to its net charge and the distribution of charge along the largely linear homogalacturonan (HG) regions of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…More recently some attention has been turned towards the more neutral, uncharged, methylesterified domains of pectin HG regions (Leijdekkers, Sanders, Schols, & Gruppen, 2011;Ralet et al, 2012;Remoroza, Buchholt, et al, 2014). These methylester protected domains (MPD) also have both biological and technological significance because they are capable of participating in hydrogen bonding and hydrophobic interactions between adjacent pectin molecules (Oakenfull & Scott, 1984;Tromp et al, 2004;Vincent et al, 2013) and are resistant to depolymerization by fungal endo polygalacturonases (EPGs) which are believed to require some minimal number of contiguous non methylesterified GalAs for hydrolysis to occur. Chen and Mort (1996) reported that a non methylesterified GalA tetramer was required for an Erwinia EPG to hydrolyze an HG region (Chen & Mort, 1996).…”
Section: Introductionmentioning
confidence: 99%